Defect-Passivated Photosensor Based on Cesium Lead Bromide (CsPbBr3) Perovskite Quantum Dots for Microbial Detection - Park, Jun-Hee; Kim, Hong-Rae; Kim, Moon-Ju; Song, Zhiquan; Kang, Min-Jung; Son, Dong Hee; Pyun, Jae-Chul (American Chemical Society, 2023)
A defect-passivated photosensor based on cesium lead bromide (CsPbBr3) perovskite quantum dots (QD) was fabricated using parylene films, and the photosensor was applied for the microbial detection. The CsPbBr3 perovskite QDs were synthesized to be homogeneous in size under thermodynamic control, and the perovskite QD-based photosensor was fabricated using MoS2 flakes as the electron transfer layer. In this work, a parylene film with functional groups was deposited on a photosensor for physical protection (waterproof) and defect (halide vacancy) passivation of the perovskite QD. As the first effect of the parylene film, the physical protection of the perovskite QD from water was estimated by comparing the photosensor performance after incubation in water. As the second effect of the parylene, the interaction between the functional groups of the parylene film and the halide vacancies of the perovskite QDs was investigated through the bandgap, crystal structure, and trap-state density analysis. Additionally, density functional theory analysis on Mulliken charges, lattice parameters, and Gibbs free energy demonstrated the effect of the defect passivation by parylene films. Finally, the parylene-passivated QD-based photosensor was applied to the detection of two kinds of food-poisoning and gastroduodenal disease bacteria (Listeria monocytogenes and Helicobacter pylori).